Analysis of Follow-Up Activity in Guidance and Counseling for Better Service Accountability - Rohman, Yuni Nur; Suherman, Uman (citeus, 2025)
Follow-up in guidance and counseling is carried out to improve and develop the quality of services or program effectiveness as well as ensuring accountability for the services provided. As a form of accountability, follow-up activities are an essential process that can ensure that the goals and objectives of these programs are achieved, the services provided are of high quality and relevant to student needs, and the services provided can be accounted for. This study examines and evaluates the effectiveness of process follow-up in schools as a means of ensuring the accountability of guidance and counseling services. The research methodology employed was a case study with an embedded single case-study design. The study participants were three high schools in Bandung, Indonesia, selected based on a purposive sampling technique. The findings indicate that the follow-up guidance and counseling activity, particularly in the three selected schools, has not been implemented correctly. This is due to a failure to adhere to the prescribed procedures and guidelines for follow-up activities.